Ebola disease: bridging scientific discoveries and clinical application - Rojek, A; Fieggen, J; Apiyo, P; Caluwaerts, S; Fowler, RA; Kaleebu, P; Kojan, R; Lado, M; Lambe, T; Dunning, J; Horby, P (Elsevier, 2024)
The west Africa Ebola disease epidemic (2014–16) marked a historic change of course for patient care during emerging infectious disease outbreaks. The epidemic response was a failure in many ways—a slow, cumbersome, and disjointed effort by a global architecture that was not fit for purpose for a rapidly spreading outbreak. In the most affected countries, health-care workers and other responders felt helpless—dealing with an overwhelming number of patients but with few, if any, tools at their disposal to provide high-quality care. These inadequacies, however, led to attention and innovation. The decade since then has seen remarkable achievements in clinical care for Ebola disease, including the approval of the first vaccines and treatments. In this paper, the first in a two-part Series, we reflect on this progress and provide expert summary of the modern landscape of Ebola disease, highlighting the priorities and ongoing activities aimed at further improving patient survival and wellbeing in the years ahead.